Expression of leukemia inhibitory factor in the endometrium in abnormal uterine cavities during the implantation window - Hasegawa, Ei; Ito, Hiroe; Hasegawa, Fumiko; Hatano, Keiko; Kazuka, Masahiro; Usuda, Saburo; Isaka, Keiichi (Fertility and sterility, 2012)
To investigate the expression of the implantation factors leukemia inhibitory factor (LIF), interleukin-11 (IL-11), and IL-6ST/gp130 in the endometrium to examine the relationship between loss of implantation and abnormal uterine cavity. Case-control study. Department of Obstetrics and Gynecology, Tokyo Medical University. Subjects comprised 41 patients in the abnormal uterine cavity group who underwent resection of a uterine submucosal myoma or an endometrial polyp by transcervical resectoscopy (TCR) and 18 patients in the control group who underwent laparoscopic surgery. In the abnormal uterine cavity group, endometrial tissue specimens were obtained before resection under hysteroscopy. In the control group, endometrial tissue specimens were obtained by curettage at the time of laparoscopic surgery. We divided the patients into four groups according to menstrual cycle and measured the endometrial expression of LIF, IL-11, and IL-6ST/gp130 with the use of quantitative real-time reverse-transcription polymerase chain reaction. Significant increases in LIF and IL-11 mRNA expression were recognized during the midsecretory phase of the menstrual cycle in the control group. However, no difference in IL-6ST/gp130 mRNA expression was observed in any phase during the menstrual cycle in either group. In terms of LIF and IL-11 mRNA expression at the midsecretory phase, the abnormal uterine cavity group showed a significantly decreased LIF mRNA expression compared with the control group. LIF mRNA expression was significantly decreased in abnormal uterine cavities during the midsecretory phase, indicating that endometrial cavity defects are a possible cause of poor reproductive outcomes.